Enhancing electron transfer of a semiconducting polymer for type I photodynamic and photothermal synergistic therapy - Cui, Cao; Su, Xuehua; Guo, Yongchun; Zhu, Jun; Chen, Zimeng; Qin, Wei; Guo, Yihang; Tao, Wenming (Frontiers in Bioengineering and Biotechnology, 2022)
Tumor hypoxia is responsible for the diminished therapeutic efficacy of type II photodynamic therapy (PDT) because of the dependence of cellular oxygen during 1O2 generation. Type I PDT may be a better strategy to overcome the disadvantages of hypoxia for enhanced theranostics. Herein a new semiconducting polymer PDPP was synthesized and encapsulated with hydrophilic PEG-PDPA to enhance the electron transfer for type I PDT. PDPP NPs show high superoxide radical generation ability with DHR123 as a probe. In vitro MTT assay indicate PDPP NPs with considerably high phototoxicity on human cervical cancer cells (HeLa) with a low half maximum inhibitory concentration (IC50) of 6.1 μg/mL. Further, in vivo study demonstrates that PDPP NPs can lead to complete tumor suppression with the help of laser, compared with the control and dark group. The biosafety is confirmed by the H&E analysis of the normal tissues (heart, liver, spleen, lung and kidney). The results provide a strategy to design nanosystem for type I PDT and PTT synergistic therapy.